2005
DOI: 10.2343/geochemj.39.113
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reaction of Tl in aqueous solution and its environmental significance

Abstract: The valence state of thallium determines its toxicity, distribution and mobility. Tl(I) can be oxidized to Tl(III) under photoirradiation of the high-pressure mercury arc lamp and solar light. A photooxidation experiment of thallium showed that the photooxidation rate could be affected by the pH of the solution, and the intensity and wavelength of the light source. Lowering the pH and increasing the light intensity have the effect of increasing the photooxidation rate. UV radiation (UVB and UVC regions) plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These results were first contested but finally confirmed by Twining et al who demonstrated that this thermodynamic disequilibrium was related to bacterial activity; indeed, these authors showed that microorganisms originating from lake and pond waters oxidize Tl(I) into Tl(III) which is believed to be subsequently stabilized by complexation with organic or inorganic substances or formation of dimethylthallium . Oxidation of Tl(I) can also take place when it is exposed to UV irradiation or sunlight. , …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These results were first contested but finally confirmed by Twining et al who demonstrated that this thermodynamic disequilibrium was related to bacterial activity; indeed, these authors showed that microorganisms originating from lake and pond waters oxidize Tl(I) into Tl(III) which is believed to be subsequently stabilized by complexation with organic or inorganic substances or formation of dimethylthallium . Oxidation of Tl(I) can also take place when it is exposed to UV irradiation or sunlight. , …”
Section: Introductionmentioning
confidence: 81%
“…14 Oxidation of Tl(I) can also take place when it is exposed to UV irradiation or sunlight. 15,16 Knowledge of Tl speciation is of primary importance to evaluate the mobility of Tl in the environment. The geochemical behavior of Tl(I) is very similar to that of K þ , showing great mobility in soils and natural waters.…”
Section: ' Introductionmentioning
confidence: 99%
“…In general the Tl + ion is the dominant species over the Eh-pH space where water is stable (Vink, 1993) whilst Tl +3 can arise from Tl + oxidation by manganese oxides (Bidoglio et al, 1993), photoinduced oxidation (Li et al, 2005) or from bacterial activity (Lin and Nriagu, 1999). The geochemistry of Tl + is somewhat enigmatic with the Tl + cation displaying both lithophilic character, such as replacing K + in silicates, as well as chalcophilic behaviour with an affinity for sulphides (Kaplan and Mattigod, 1998;Hettmann et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Metals oxidation cycles in natural waters are often mediated by photochemical processes (Allen et al, 1996;Zafiriou et al, 1984). Some authors observed that the oxidation of Tl(I) in aqueous solutions can take place during UV or sunlight irradiation (Karlsson et al, 2006;Li et al, 2005), thanks to the production of possible oxidative species such as hydrogen peroxide or •OH (Paul, 2001). Especially the highly reactive transient hydroxyl radicals might represent strong oxidants, considering that the production of hydroxyl radicals is speeded up by Fe(II) generated by photoreduction (photo-Fenton reactions).…”
Section: Introductionmentioning
confidence: 99%